Career Satisfaction Based on Trust and Proactive Personality - Sunardi, Iwan; Putri, Vini Wiratno (Management Analysis Journal, 2020)
The purpose of this study was to examine the effect of the trust of co-workers and proactive personalities on career satisfaction by exchanging leader-members as mediation on employees of bus assembly companies in the city of Semarang. Career satisfaction is the phase in which employees’ long-term career needs are aligned with what they get while working. Employees will always look for opportunities and trust in the organization and people who will help them in achieving career satisfaction. The sampling method uses a purposive sampling technique in the category of staff and foreman employees who have worked for more than five years with a sample of 160 employees. The analytical data in this study uses descriptive statistical test methods, instinctual tests include validity and reliability, and hypothesis testing. The tool used to test in this study uses SmartPLS 3.0. The results of this study, colleague trust cannot directly influence career satisfaction. However, it can be mediated by the exchange of leader members and produce significant influence. For further researchers, they can re-examine the relationship of coworkers’ trust with career satisfaction. And can expand the object of research or respondents under study.